Rasd1, a small G protein with a big role in the hypothalamic response to neuronal activation. Issue 1 (December 2016) - Greenwood, Michael; Greenwood, Mingkwan; Mecawi, Andre; Antunes-Rodrigues, José; Paton, Julian; Murphy, David
Abstract Background Rasd1 is a member of theRas family of monomeric G proteins that was first identified as a dexamethasone inducible gene in the pituitary corticotroph cell line AtT20. Using microarrays we previously identified increasedRasd1 mRNA expression in the rat supraoptic nucleus (SON) and paraventricular nucleus (PVN) of the hypothalamus in response to increased plasma osmolality provoked by fluid deprivation and salt loading. RASD1 has been shown to inhibit adenylyl cyclase activity in vitro resulting in the inhibition of the cAMP-PKA-CREB signaling pathway. Therefore, we tested the hypothesis that RASD1 may inhibit cAMP stimulated gene expression in the brain. Results We show thatRasd1 is expressed in vasopressin neurons of the PVN and SON, within which mRNA levels are induced by hyperosmotic cues. Dexamethasone treatment of AtT20 cells decreased forskolin stimulation ofc-Fos, Nr4a1 and phosphorylated CREB expression, effects that were mimicked by overexpression ofRasd1, and inhibited by knockdown ofRasd1 . These effects were dependent upon isoprenylation, as both farnesyltransferase inhibitor FTI-277 and CAAX box deletion preventedRasd1 inhibition of cAMP-induced gene expression. Injection of lentiviral vector into rat SON expressingRasd1 diminished, whereas CAAX mutant increased, cAMP inducible genes in response to osmotic stress. Conclusions We have identified two mechanisms ofRasd1 induction in the hypothalamus, one by elevated glucocorticoids in response to stress, and one in response to increased plasma osmolality resulting from osmotic stress. We propose that the abundance of RASD1 in vasopressin expressing neurons, based on its inhibitory actions on CREB phosphorylation, is an important mechanism for controlling the transcriptional responses to stressors in both the PVN and SON. These effects likely occur through modulation of cAMP-PKA-CREB signaling pathway in the brain.